2020
DOI: 10.3390/met11010062
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of Graphene Nanoplatelets-Reinforced Mg-3Sn Alloy Synthesized by Powder Metallurgy

Abstract: The present study investigated the effects of alloying and nano-reinforcement on the mechanical properties (microhardness, tensile strength, and compressive strength) of Mg-based alloys and composites. Pure Mg, Mg-3Sn alloy, and Mg-3Sn + 0.2 GNP alloy-nanocomposite were synthesized by powder metallurgy followed by hot extrusion. The microstructural characteristics of the bulk extruded samples were explored using X-ray diffraction, field-emission scanning electron microscopy, and optical microscopy and their me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Friction stir processing (FSP) is a promising method for solid-state processing that can achieve homogeneous distribution of CNT on surfaces without melting the matrix material [3]. The powder metallurgy (PM) process requires fewer complex steps to achieve the dispersion of a larger number of nanoparticles, while being more economical and saving more time and materials [56]. Ultrasonic treatment assisted with semi-solid stirring can break agglomerations by ultrasonic waves [57].…”
Section: Carbon-reinforced Mg-based Compositesmentioning
confidence: 99%
“…Friction stir processing (FSP) is a promising method for solid-state processing that can achieve homogeneous distribution of CNT on surfaces without melting the matrix material [3]. The powder metallurgy (PM) process requires fewer complex steps to achieve the dispersion of a larger number of nanoparticles, while being more economical and saving more time and materials [56]. Ultrasonic treatment assisted with semi-solid stirring can break agglomerations by ultrasonic waves [57].…”
Section: Carbon-reinforced Mg-based Compositesmentioning
confidence: 99%
“…The major portion of MMC's is the matrix material, as it gives shape to the composite and binds the reinforcement particles along with it. Aluminum, magnesium, copper, iron, and titanium are commonly used matrix for the fabrication of MMCs [10][11][12][13][14].…”
Section: Matrix Materialsmentioning
confidence: 99%
“…About 90% of commercial Mg alloys combining sufficient room temperature strength, ductility, and improved corrosion resistance are cast alloys. The most widely used traditional Mg alloys are aluminum-zinc (AZ60, AZ91) and aluminum-manganese (AM50, AM60) systems because of their presence of Al for enhanced castability [10]. However, the formation of a thermally unstable β-phase, i.e., Mg 17 Al 12 , in these systems restricts their use for applications such as automotive powertrain components requiring high strength and wear resistance at elevated temperatures [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The open literature sources suggest that the use of GNP reinforcement in Al-free Mg alloys has been rarely studied, and those studies employing powder-metallurgy-based fabrication methods concentrated on only the investigation of mechanical properties. Kumar et al [10] found that the addition of 0.2 wt.% GNPs (6-10 nm in thickness and 15 µm in average lateral size) into Mg-3Sn alloy improved the microhardness and ultimate tensile strength by 7.8 and 9%, respectively. Wang et al [33] reported that the yield strength and toughness of Mg-5.20Zn-0.33Zr (ZK60) alloy were enhanced with 0.1 wt.% GNP (3-10 nm in thickness, 1-7 µm in lateral size) content by 52 and 19%, respectively.…”
Section: Introductionmentioning
confidence: 99%